Full-degradable modified film bag material and preparation method thereof
By using hydrophobic modified straw cellulose nano-long fibers and modified epoxy soybean oil in PBAT film bag materials, the problem of weak and easy to break in the mechanical strength of PBAT film bag materials is solved, and the material strength is significantly improved and the cost is achieved. reduce.
Patent Information
- Application Number
- CN202411451716.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polyadipate-butylene terephthalate (PBAT) film bag materials have weak mechanical strength and are easy to break, have small amount of starch added and are incompatible with the matrix, resulting in a material strength less than 10MPa and a short shelf life.
Hydrophobically modified straw cellulose nano-long fibers are used as mechanical reinforcement, and the interface compatibility and adhesion between starch and matrix resin is improved by modifying epoxy soybean oil to form a crosslinking network structure, thereby enhancing the mechanical strength of the material. .
The tensile strength and elongation of the polyadipic acid-butylene terephthalate composite film bag material have been significantly improved, reaching performance indicators of 16.4-25.8MPa and 277-470%, while reducing production costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biodegradable polymer packaging materials, and in particular relates to a method for preparing a fully degradable modified film bag material. Background Art
[0002] Polybutylene adipate-terephthalate (PBAT) can be almost completely decomposed by microorganisms and has become an emerging material in the fields of packaging, medical and agricultural films. Polybutylene adipate-terephthalate (PBAT) has both the flexibility of long methylene chains and the rigidity of aromatic rings. It has good biodegradability and can meet the requirements of the EU compostable plastic standard EN13432 that the biodegradation rate is not less than 90% within 180 days. It also has excellent mechanical properties. The glass transition temperature of PBAT is −30-−35℃, the melting temperature is 110-130℃, and the processing performance is similar to that of low-density polyethylene (LDPE). The film bags prepared by blow molding have good tensile strength, flexibility and heat sealing properties, but the material cost is higher than that of traditional petrochemical raw materials. A large amount of calcium carbonate and starch are usually added to reduce the material cost of the film bag. PBAT film bags with calcium carbonate are usually dense, brittle, easy to break, and thick, so PBAT film bags gradually use thermoplastic starch instead of calcium carbonate. Starch is a kind of degradable natural polymer material with advantages such as wide sources, low price, and easy biodegradation. However, the hydrophilic starch has poor interfacial compatibility with the PBAT matrix, the interfacial adhesion between the components is low, and the starch is prone to yellowing and degradation during thermoplastic processing, resulting in the existing commercially available PBAT film bags having shortcomings such as weak strength, easy puncture, mechanical strength less than 10MPa, and short shelf life. The polylactic acid (PLLA) content is usually supplemented to improve the overall strength of the PBAT film bag, which further increases the cost. Therefore, it is necessary to develop new technologies to achieve compatibility between starch and the PBAT matrix, increase the starch content, and at the same time improve the strength of the PBAT film bag and control the cost. Summary of the invention
[0003] In order to solve the problems of weak mechanical strength, easy breakage, small amount of starch addition, incompatibility of starch with the matrix, etc. of the existing poly (butylene adipate-terephthalate) (PBAT) film bag material, the present invention provides a method for preparing a fully degradable modified film bag material.
[0004] The preparation steps of a fully degradable modified film bag material are as follows:
[0005] (1) Preparation of modified epoxidized soybean oil
[0006] 60-70 parts by weight of epoxy soybean oil, 30-40 parts by weight of sebacic acid and 0.01-0.03 parts by weight of p-dimethylaminopyridine (DMAP) are mixed and reacted at a temperature of 170-190° C. for 40-80 minutes to obtain modified epoxy soybean oil (VESO); the epoxy value of the epoxy soybean oil is 60 mol / 100 g;
[0007] (2) Preparation of pre-dispersed mixture
[0008] 50-65 parts by weight of dried polybutylene adipate-terephthalate (PBAT), 2-8 parts by weight of high molecular weight polylactic acid (PLLA), 15-40 parts by weight of corn starch, 0-3 parts by weight of modified straw cellulose nano-fiber reinforcing agent, 5-10 parts by weight of modified epoxidized soybean oil (VESO), 1-2 parts by weight of chain extender and 0.5-1 parts by weight of antioxidant are fully mixed in a high-speed mixer to obtain a pre-dispersed mixture;
[0009] The polybutylene adipate-terephthalate (PBAT) has a melt index of 3-10 g / 10 min and a carboxyl content of 10-30 mol / t;
[0010] The high molecular weight polylactic acid (PLLA) has a weight average molecular weight of 80,000-150,000 g / mol and a polydispersity coefficient of 1.2-2;
[0011] The modified straw cellulose nano-long fiber reinforcing agent is prepared by subjecting a wheat straw cellulose acid hydrolyzed aqueous suspension to 10 high pressure homogenization cycles at 100 MPa, followed by hydrophobic modification and freeze drying.
[0012] The chain extender is an epoxy chain extender or a diisocyanate chain extender;
[0013] The antioxidant is at least one of antioxidant 3114, antioxidant 1010, antioxidant 168, and antioxidant 1076;
[0014] (3) Preparation of fully biodegradable modified membrane bag materials
[0015] In a counter-rotating twin-screw extruder, the pre-dispersed mixture is melt-kneaded for 4-10 minutes to be extruded in situ, cooled and pelletized to obtain a fully degradable modified film bag material;
[0016] The fully degradable modified film bag material has a tensile strength of 16.4-25.8 MPa and an elongation at break of 277-470%.
[0017] The further technical solution is as follows:
[0018] In step (2), the preparation steps of the modified straw cellulose nano-long fiber reinforcing agent are as follows:
[0019] (1.1) Spray a 1.5-5 mol / L diluted hydrochloric acid solution three times the mass of the wheat straw powder on the wheat straw powder, stir and react at 60-100°C for 6-10 hours to obtain a micro-nano loosened straw cellulose aqueous suspension;
[0020] (1.2) In a high-pressure homogenizer, the micro-nano loosened straw cellulose aqueous suspension is subjected to high-pressure homogenization cycle treatment at 100 MPa for 10 times to obtain a 2 wt% straw cellulose nanofiber suspension slurry with high heat stability and no charge;
[0021] (1.3) Hexadecyltrimethoxysilane in an amount five times the molar number of cellulose glucose units in the straw cellulose nanofiber suspension was added to a 2 wt % straw cellulose nanofiber suspension, and the mixture was reacted at 60 ° C for 8 h. The mixture was freeze-dried to obtain a white powdery hydrophobic long-chain modified straw cellulose nanofiber reinforcement agent with a fiber diameter of 15-50 nm, an aspect ratio of 400-500, and a water contact angle of 120 ° C, showing hydrophobicity.
[0022] In step (2), the chain extender is specifically at least one of ADR4468, ADR4400, hexamethylene diisocyanate, toluene diisocyanate, and 4,4'-diphenylmethane diisocyanate.
[0023] In step (2), in the high-speed mixer, the rotation speed is 300-800 rpm and the mixing time is 10-30 min.
[0024] In step (3), the length-to-diameter ratio of the counter-rotating twin-screw extruder is 40:1, the screw speed is 50-200 rpm, and the temperatures from the feeding section to the die are 155°C, 160°C, 165°C, 165°C, 165°C, and 160°C, respectively.
[0025] Compared with the prior art, the beneficial technical effects of the present invention are embodied in the following aspects:
[0026] (1) The present invention uses hydrophobically modified straw cellulose nanofibers as a mechanical enhancer. On the one hand, the glucose main chain of straw cellulose has a similar main chain structure to starch and has good affinity with starch. On the other hand, the long chain side groups of the modified straw cellulose nanofibers have good affinity and compatibility with polybutylene adipate terephthalate and polylactic acid resin matrices. Therefore, adding a trace amount of modified straw cellulose nanofibers can greatly improve the mechanical strength of the polybutylene adipate terephthalate composite film bag material.
[0027] (2) Traditionally, polybutylene adipate-terephthalate and polylactic acid have used epoxy soybean oil as a crosslinking agent. However, due to its strong flexibility, a large amount of polylactic acid is usually required to ensure mechanical strength. The present invention modifies the epoxy soybean oil. The rich carboxyl and epoxy groups on the modified epoxy soybean oil can react with the terminal hydroxyl groups and carboxyl groups on polylactic acid and polybutylene adipate-terephthalate, as well as the hydroxyl groups on starch. Through the reaction, the modified epoxy soybean oil introduces a crosslinking network structure into the system, thereby improving the interfacial compatibility between starch and the matrix resin. At the same time, the methylene groups on the modified epoxy soybean oil have good compatibility with polybutylene adipate-terephthalate and polylactic acid matrices, thereby improving the interfacial adhesion between polybutylene adipate-terephthalate and polylactic acid and starch, thereby enhancing the mechanical strength of the composite material at a low polylactic acid content. When the same strength requirements are met, the film bag can be blown thinner, thereby ultimately achieving lightweight and significantly reducing production costs. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below by way of examples.
[0029] The sources of the raw materials used in the following examples are described as follows:
[0030] Polybutylene adipate terephthalate (PBAT) resin comes from Donghua Engineering Technology Co., Ltd., and polylactic acid (PLLA) resin comes from Fengyuan Group Co., Ltd.
[0031] The preparation process of the modified straw cellulose nano-fiber powder reinforcing agent used in the following examples is as follows:
[0032] (1) Spray a 1.5 mol / L dilute hydrochloric acid solution three times the mass of the wheat straw powder on the wheat straw powder, stir at 100°C for 10 h, and obtain a micro-nano loosened straw cellulose aqueous suspension.
[0033] (2) The cellulose was put into a high-pressure homogenizer and subjected to 10 cycles of high-pressure homogenization treatment at 100 MPa to obtain a 2 wt% concentration of straw cellulose nanofiber suspension pulp with high heat resistance and stability and no charge.
[0034] (3) Add hexadecyltrimethoxysilane in an amount five times the molar number of cellulose glucose units in the straw cellulose nanofiber suspension to the straw cellulose nanofiber suspension, react at 60°C for 8 h, wash with water for purification, and freeze-dry at -60°C to obtain a white powdery hydrophobic long-chain modified straw cellulose nanofiber reinforcement agent with a fiber diameter of 15-50 nm, an aspect ratio of 400-500, and a water contact angle of 120°, showing hydrophobicity, for standby use.
[0035] Example 1
[0036] The preparation steps of a fully degradable modified film bag material are as follows:
[0037] (1) Preparation of modified epoxidized soybean oil
[0038] 60g of epoxy soybean oil, 30g of sebacic acid and 0.01g of p-dimethylaminopyridine (DMAP) were mixed and reacted in an oil bath at a temperature of 190°C for 40 minutes to obtain modified epoxy soybean oil (VESO); the epoxy value of the epoxy soybean oil was 60mol / 100g.
[0039] (2) Preparation of pre-dispersed mixture
[0040] Weigh 62g of polybutylene adipate terephthalate (PBAT), 7g of polylactic acid (PLLA), 25g of corn starch, 5g of modified epoxidized soybean oil (VESO), 1g of modified straw cellulose nanofiber reinforcement powder, 1g of chain extender ADR4468 and 0.5g of antioxidant 3114, and mix them thoroughly in a high-speed mixer at 500rpm at room temperature for 20min to obtain a pre-dispersed mixture.
[0041] (3) Preparation of fully biodegradable modified membrane bag materials
[0042] The pre-dispersed mixture was added into a counter-rotating twin-screw extruder with a length-to-diameter ratio of 40:1. The screw speed was 100 rpm. The temperatures from the feeding section to the die of the twin-screw extruder were 155°C, 160°C, 165°C, 165°C, 165°C, and 160°C, respectively. The mixture was first mixed for 4 minutes to melt and mix the materials in the pre-dispersed mixture and complete the in-situ reaction. The mixture was then extruded and granulated to obtain a fully degradable modified film bag material.
[0043] The fully degradable modified film bag material prepared in Example 1 has a tensile strength of 20.4 MPa and an elongation at break of 375%.
[0044] Example 2
[0045] (1) Preparation of modified epoxidized soybean oil
[0046] 70g of epoxy soybean oil, 40g of sebacic acid and 0.02g of dimethylaminopyridine (DMAP) were mixed and reacted in an oil bath at a temperature of 180°C for 60 minutes to obtain modified epoxy soybean oil (VESO); the epoxy value of the epoxy soybean oil was 60mol / 100g.
[0047] Step (2) and step (3) of this embodiment 2 are the same as step (2) and step (3) of embodiment 1.
[0048] The fully degradable modified film bag material prepared in Example 2 has a tensile strength of 18.5 MPa and an elongation at break of 421%.
[0049] Example 3
[0050] (1) Preparation of modified epoxidized soybean oil
[0051] 70g of epoxy soybean oil, 30g of sebacic acid and 0.03g of p-dimethylaminopyridine (DMAP) were mixed and reacted in an oil bath at a temperature of 170°C for 80 minutes to obtain modified epoxy soybean oil; the epoxy value of the epoxy soybean oil was 60mol / 100g.
[0052] Step (2) and step (3) of this embodiment 3 are the same as step (2) and step (3) of embodiment 1.
[0053] The fully degradable modified film bag material prepared in Example 3 has a tensile strength of 17.0 MPa and an elongation at break of 470%.
[0054] By comparing the tensile strength and elongation at break results of the modified film bag materials prepared in Examples 1, 2, and 3, it can be seen that different formulations of modified epoxidized soybean oil (VESO) affect the strength of the composite material, and the fully degradable modified film bag material prepared in Example 1 has the best mechanical strength. Therefore, the following examples all adopt the preparation formula of modified epoxidized soybean oil (VESO) in Example 1.
[0055] Example 4
[0056] The difference between Example 4 and Example 1 is that in step (2), the modified epoxidized soybean oil (VESO) is replaced by unmodified epoxidized soybean oil (ESO).
[0057] The fully degradable modified film bag material prepared in Example 4 has a tensile strength of 15.1 MPa and an elongation at break of 348%.
[0058] Example 5
[0059] The difference between Example 5 and Example 1 is that in step (2), modified epoxidized soybean oil (VESO) or epoxidized soybean oil (ESO) is not added.
[0060] The fully degradable modified film bag material prepared in Example 5 has a tensile strength of 16.4 MPa and an elongation at break of 297%.
[0061] Comparing the tensile strength and elongation at break of the modified film bag materials prepared in Examples 1, 4, and 5, it can be seen that the use of modified epoxy soybean oil (VESO) as a compatibilizer can achieve better results than unmodified epoxy soybean oil (ESO) and no addition of any compatibilizer. Simply adding unmodified epoxy soybean oil (ESO) will reduce the mechanical strength of the composite material, so the polylactic acid (PLLA) content is usually high. In this Example 1, effective cross-linking is generated by adding modified epoxy soybean oil (VESO), thereby improving the mechanical strength of the modified film bag material.
[0062] Example 6
[0063] The difference between Example 6 and Example 1 is that in step (2), the amount of modified straw cellulose nanofiber powder added is reduced to 0.5 g.
[0064] The fully degradable modified film bag material prepared in Example 6 has a tensile strength of 19.0 MPa and an elongation at break of 390%.
[0065] Example 7
[0066] The difference between Example 7 and Example 1 is that in step (2), no modified straw cellulose nanofiber powder is added.
[0067] The fully degradable modified film bag material prepared in Example 7 has a tensile strength of 16.9 MPa and an elongation at break of 321%.
[0068] By comparing the tensile strength results of the modified film bag materials prepared in Examples 1, 6, and 7, it can be seen that the reinforcement effect when the addition amount of the modified straw cellulose nano-long fiber reinforcing agent is 1 mass part is better than the reinforcement effect of 0.5 mass part and without adding the reinforcing agent, indicating that the tensile strength of the modified film bag material can be enhanced by adding the modified straw cellulose nano-long fiber reinforcing agent.
[0069] Example 8
[0070] The difference between Example 8 and Example 1 is that in step (2), 50 g of polybutylene adipate-terephthalate (PBAT) and 10 g of modified epoxidized soybean oil (VESO) are weighed.
[0071] The fully degradable modified film bag material prepared in Example 8 has a tensile strength of 19.2 MPa and an elongation at break of 277%.
[0072] Example 9
[0073] The difference between Example 9 and Example 1 is that in step (2), 57 g of polybutylene adipate-terephthalate (PBAT) and 6.5 g of modified epoxidized soybean oil (VESO) are weighed.
[0074] The fully degradable modified film bag material prepared in Example 9 has a tensile strength of 21.9 MPa and an elongation at break of 322%.
[0075] Example 10
[0076] The difference between Example 10 and Example 1 is that in step (2), 65 g of polybutylene adipate-terephthalate (PBAT) and 8.5 g of modified epoxidized soybean oil (VESO) are weighed.
[0077] The fully degradable modified film bag material prepared in Example 10 has a tensile strength of 22.6 MPa and an elongation at break of 397%.
[0078] Embodiment 11
[0079] The difference between Example 11 and Example 1 is that in step (2), 1.5 g of chain extender ADR4400 and 0.5 g of antioxidant 1010 are weighed.
[0080] The fully degradable modified film bag material prepared in Example 11 has a tensile strength of 23.5 MPa and an elongation at break of 345%.
[0081] Example 12
[0082] The difference between Example 12 and Example 1 is that in step (2), 1 g of chain extender hexamethylene diisocyanate and 1 g of antioxidant 168 are weighed.
[0083] The fully degradable modified film bag material prepared in Example 12 has a tensile strength of 24.0 MPa and an elongation at break of 359%.
[0084] Embodiment 13
[0085] The difference between Example 13 and Example 1 is that in step (2), 1 g of chain extender toluene diisocyanate and 1 g of antioxidant 1076 are weighed.
[0086] The fully degradable modified film bag material prepared in Example 13 has a tensile strength of 25.8 MPa and an elongation at break of 284%.
[0087] Embodiment 14
[0088] The difference between Example 14 and Example 1 is that in step (2), 1 g of chain extender 4,4'-diphenylmethane diisocyanate and 1 g of antioxidant 1076 are weighed.
[0089] The fully degradable modified film bag material prepared in Example 14 has a tensile strength of 23.2 MPa and an elongation at break of 409%.
Claims
1. A method for preparing a fully degradable modified film bag material, characterized in that: The steps are as follows: (1) Preparation of modified epoxidized soybean oil 60-70 parts by weight of epoxy soybean oil, 30-40 parts by weight of sebacic acid and 0.01-0.03 parts by weight of p-dimethylaminopyridine (DMAP) are mixed and reacted at a temperature of 170-190° C. for 40-80 minutes to obtain modified epoxy soybean oil (VESO); the epoxy value of the epoxy soybean oil is 60 mol / 100 g; (2) Preparation of pre-dispersed mixture 50-65 parts by weight of dried polybutylene adipate-terephthalate (PBAT), 2-8 parts by weight of high molecular weight polylactic acid (PLLA), 15-40 parts by weight of corn starch, 0-3 parts by weight of modified straw cellulose nano-fiber reinforcing agent, 5-10 parts by weight of modified epoxidized soybean oil (VESO), 1-2 parts by weight of chain extender and 0.5-1 parts by weight of antioxidant are fully mixed in a high-speed mixer to obtain a pre-dispersed mixture; The polybutylene adipate-terephthalate (PBAT) has a melt index of 3-10 g / 10 min and a carboxyl content of 10-30 mol / t; The high molecular weight polylactic acid (PLLA) has a weight average molecular weight of 80,000-150,000 g / mol and a polydispersity coefficient of 1.2-2; The modified straw cellulose nano-long fiber reinforcing agent is prepared by subjecting a wheat straw cellulose acid hydrolyzed aqueous suspension to 10 high pressure homogenization cycles at 100 MPa, followed by hydrophobic modification and freeze drying. The chain extender is an epoxy chain extender or a diisocyanate chain extender; The antioxidant is at least one of antioxidant 3114, antioxidant 1010, antioxidant 168, and antioxidant 1076; (3) Preparation of fully biodegradable modified membrane bag materials In a counter-rotating twin-screw extruder, the pre-dispersed mixture is melt-kneaded for 4-10 minutes to be extruded in situ, cooled and pelletized to obtain a fully degradable modified film bag material; The fully degradable modified film bag material has a tensile strength of 16.4-25.8 MPa and an elongation at break of 277-470%.
2. The method for preparing a fully degradable modified film bag material according to claim 1, characterized in that: In step (2), the preparation steps of the modified straw cellulose nano-fiber reinforcing agent are as follows: (1.1) Spray a 1.5-5 mol / L diluted hydrochloric acid solution three times the mass of the wheat straw powder on the wheat straw powder, stir and react at 60-100°C for 6-10 hours to obtain a micro-nano loosened straw cellulose aqueous suspension; (1.2) In a high-pressure homogenizer, the micro-nano loosened straw cellulose aqueous suspension is subjected to high-pressure homogenization cycle treatment at 100 MPa for 10 times to obtain a 2 wt% straw cellulose nanofiber suspension slurry with high heat stability and no charge; (1.3) Hexadecyltrimethoxysilane in an amount five times the molar number of cellulose glucose units in the straw cellulose nanofiber suspension was added to a 2 wt % straw cellulose nanofiber suspension, and the mixture was reacted at 60 ° C for 8 h. The mixture was freeze-dried to obtain a white powdery hydrophobic long-chain modified straw cellulose nanofiber reinforcing agent with a fiber diameter of 15-50 nm, an aspect ratio of 400-500, and a water contact angle of 120 ° C, showing hydrophobicity.
3. The method for preparing a fully degradable modified film bag material according to claim 1, characterized in that: In step (2), the chain extender is specifically at least one of ADR4468, ADR4400, hexamethylene diisocyanate, toluene diisocyanate, and 4,4'-diphenylmethane diisocyanate.
4. The method for preparing a fully degradable modified film bag material according to claim 1, characterized in that: In step (2), in the high-speed mixer, the rotation speed is 300-800 rpm and the mixing time is 10-30 min.
5. The method for preparing a fully degradable modified film bag material according to claim 1, characterized in that: In step (3), the aspect ratio of the counter-rotating twin-screw extruder is 40:1, the screw speed is 50-200 rpm, and the temperatures from the feeding section to the die are 155°C, 160°C, 165°C, 165°C, 165°C, and 160°C, respectively.